Motivasi Spiritual Pada Kegiatan Kultum Ramadhan di Masjid dan Musholla Perkotaan Studi Partisipasi Riset di Masjid dan Musholla Surabaya - Alaika Muhammad, Alaika M. Bagus Kurnia PS (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2025)
Community service activities related to spiritual motivation for urban congregations are motivated by how their lives are in the midst of their busy work activities. So this activity aims to restore the dignity of places of worship such as mosques and prayer rooms as primary places of worship for urban communities. This method uses participatory action research, namely researchers as well as the main actors in carrying out spiritual motivation activities. The locus of this activity is in mosques and prayer rooms, private institutions, to universities and one state junior high school in Surabaya. The results of this activity, the community became more active in carrying out congregational prayers, the initiative to hold a taklim assembly in mosques and prayer rooms also came from the community, not from the administrators of mosques and prayer rooms, until religious life was felt by the community after the month of Ramadan